Adaptation of Cultivating Awareness and Resilience in Education (CARE) Program to Improve Social-Emotional Competence (SEC) Educarer in Child Care Parks (TPA) - Damayanti, Anak Agung Sagung Ratih; Wijaya, Nerissa; Hartanti, Hartanti (Universitas Muhammadiyah Metro, 2019)
Cultivating awareness and resilience in education (CARE Program) is a mindfulness-based training program. Aims to improve the socio-emotional competence of educators in child care centers. The training participants were invited to identify self-conditions related to stress, emotional regulation, and self-efficacy in teaching. As well as ways that can be done to improve socio-emotional competence related to teaching activities. The training program was given for two days to 19 educators ranging in age from 20-24 years. The results of the training showed that there was a significant change in the burnout level of the participants after attending the training and the training materials were felt to be more effective by educators who had taught for more than one year.